Das minas de carvão para os clubes de futebol e sociedades recreativas: experiência de classe entre o operariado da indústria carbonífera do Rio Grande do Sul (1930-1950) - Freitas, Tassiane Mélo de (2021)
This thesis is part of the Culture, Migration and Work Research Line of the Postgraduate Program in History at the Federal University of Santa Maria and deals with the comprehension of the experiences of miners in the coal region of Baixo Jacuí through leisure and sociability spaces as drivers of the class formation process. Based mainly on the theoretical perspective brought by E.P. Thompson and on the studies of the Worlds of Labor, Leisure and the Social History of Football, we investigate the formation of these spaces in places where it is possible to observe movements of domination and resistance which include the defense of the right to leisure and the meanings of the playful and sporting practices of the working class, even in the midst of class contradictions. Considering the situation that permeates the period of World War II and the Brazilian Estado Novo (New State), as well as the control of the Management Consortium of Mining Companies (Cadem) over the coal mines in the region, the working and living conditions in the region are addressed, as well as how these were formed, both at work and in spaces for leisure and sociability. Subsequently, an attempt is made to comprehend the discourse constituted around the hygienist ideology and the way it was related to the issue of sports. Thus, part of the forms of domination of Cadem is understood, including through the promotion of the development of soccer clubs in the region, especially since the end of the 1930s. Later, aspects related to conflicts within the class are and the discontinued solidarity among miners are discussed. Finally, the heterogeneous forms and spaces of resistance of the miners are analyzed, presenting the process of construction of the working class's own meanings for their playful, sociable and sports practices, opposing or even reframing the standards imposed by the hygienism propagated by Cadem. Written documents and images collected in public and personal collections, images captured in memory groups on social networks and oral documents produced through interviews were analyzed.